Chronic Noise Exposure with Normal Hearing is Related to Adverse Quality of Life and Burnout - Karaiskos, Christos; Vlastos, Ioannis; Farantos, Georgios; Rachiotis, Georgios; Simou, Effie; Dounias, Georgios (European Scientific Journal, ESJ, 2024)
Aims and scope: Occupational noise exposure is a well-known factor of hearing loss and other health related problems. Its contribution on burnout and health related quality of life, particularly when there is no hearing loss is less well studied. Herein we aim to study the effect of noise on the responses of normal hearing industrial workers on validated instruments. Methods: 384 industrial workers from three pharmaceutical companies with normal hearing were stratified into two groups: a noise-exposure group (n=195) and a non-exposure group (n=125). In addition to basic demographic characteristics, factors such as smoking, and BMI were examined alongside responses to the Oldenburg Burnout Inventory (OLBI) and SF-36 questionnaire. Findings: The noise-exposure group exhibited a higher prevalence of smokers (p<0.01), a slightly elevated median BMI (p=0.04) and reported more pronounced exhaustion as measured by the OLBI (p=0.03). Furthermore, they exhibited poorer responses in various dimensions of the SF-36 questionnaire, particularly in bodily pain (p<0.01), physical functioning (p=0.03), physical role functioning (p=0.02) and emotional role functioning (p<0.01) scales. Conclusion: Occupational noise exposure, even in the absence of hearing loss, is associated with a higher prevalence of burnout symptoms and an overall reduced health-related quality of life among industrial workers. These insights underscore the need for proactive measures to mitigate noise exposure’s adverse impact on employee well-being and productivity in noisy work environments, independently of the findings in their audiometric results.